Features of treatment of patients with complicated retention of the third molars at the inpatient stage. - Gudaryan, O. O.; Іdashkіna, N. G.; Nekhanevich, Zh. M. (Medicni Perspektivi, 2016)
The aim of the study was to define frequency of infectious-inflammatory complications of the thirds molars retention and outcomes of surgical treatment in residents of Dnipropetrovsk region on the basis of archiv materials. We surveyed 814 patients with retention of the third molars in the period from 2012 to 2015. On the basis of medical history it was revealed that lately diagnosed and treated acute pericoronaritis, is the cause of formation of severe inflammatory-infectious complications (osteomyelitis, abscess, lymphadenitis and others). Among the population of Dnipropetrovsk region the number of patients with retention of third molars, complicated withpericoronaritis is 5.8%, acute odontogenic osteomyelitis – 36.4%, chronic odontogenic osteomyelitis – 6.86%, acute odontogenic lymphadenitis – 5.8%, phlegmon – 3,4%. Standard approach in operations of atypical removal of impacted third molars causes a significant number of surgical complications (large bone defects, inflammatory contracture, post-traumatic neuritis, etc.).